ANALISIS PENGGUNAAN RAGAM JENIS PENSIL UNTUK MENGEMBANGKAN KEMAMPUAN MENGGAMBAR DENGAN TEKNIK ARSIR BAGI MAHASISWA PGSD UNJ - Fahrurrozi; Yofita Sari; Fitri Atika Putri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article analyzes the use of various types of pencils to develop drawing skills by using shading techniques for PGSD students of UNJ. The research in this article involves three pictures owned by three PGSD students of UNJ who have learnt the Elementary Art Education subject course. The study is aimed to make PGSD students of UNJ able to pay attention to the picture elements such as points, lines, sides, space, light and dark, colour gradations, and textures. In addition, students can use various types of pencils such as B-coded pencils consisting of 2B, 4B, and 6B in drawing with shading techniques in order to produce pictures that have an aesthetic value. The research is a qualitative descriptive study with documentation and interview methods. Through the use of various types of Bcoded pencils, students can fulfil the picture elements such as the effect of light-dark drawing objects, colour gradations with high to low saturation, and textures. The use of various types of pencils in drawing with shading techniques can be developed if students can be consistent practice scratching various types of pencils diligently. If the picture elements have not been seen in the picture object by using the shading technique yet, students could practice drawing again diligently.